Carbon and nitrogen winter storage and remobilisation during seasonal flush growth in two-year-old cork oak (Quercus suber L.) saplings - Cerasoli, Sofia; Maillard, Pascale; Scartazza, Andrea; Brugnoli, Enrico; Chaves, Maria Manuela; Pereira, João Santos; Erasolia, Sofia C; Aillardc, Pascale M; Cartazzad, Andrea S; Rugnolid, Enrico B; Havesa, Maria Manuela C; Ereiraa, João Santos P (Ann. For. Sci., 2004)
A dual long-term 13C and 15N labeling was used to assess the contribution of winter assimilated carbon (C) and nitrogen (N) for the spring growth flush of two-year-old cork oak plants. Changes in concentrations and partitioning of winter assimilated C and N, total C and N, and total-non-structural carbohydrates were followed from January to August in the various plant parts (first year and second year leaves, stem, branches, coarse and fine roots). No loss of winter C and N was observed with time suggesting that winter assimilates are retained within the plant and contribute to storage. A strong mobilisation of C and N was demonstrated from first year leaves and fine roots during the spring growth flush. Leaves from the second year and, to lesser extent, branches acted as sinks for winter C and N. At the beginning of the new leaf growth, a significant decrease in starch concentration occurred in first year leaves. In August, before leaf fall we observed also a mobilisation from first year to second year leaves, of N assimilated after labeling. We conclude that under these experimental conditions, both winter and current C and N were used for the spring growth flush of the cork oak plants. The foliage grown during the previous year was a source of winter and recently assimilated N and a source of C from recent assimilates for the new growth in the spring.
Keywords: 13C labeling; 15N labeling; carbohydrates; Quercus suber; remobilisation